Sustainability of animal agriculture in tropical Africa - Fitzhugh, H.A. (Alberta University, 1993)
Population pressures will expand and intensify African agriculture. By 2025, the sub-Saharan African population will exceed 1290 million, a 260 percent increase in the next three decades, and 54 percent of Africans will be living in urban environments largely dependent on others for food production. The consequent commercialization of African agriculture will promote intensification, particularly of mixed farming systems in which the livestock component provides traction, and manure as well as food family and cash from sale of livestock products. Using the World Bank goal of a 4 percent annual increase in food production, meat production from African livestock would increase from the current 4.5 million to 19.2 million metric tons in 2025 (60 percent) from ruminants; milk would increase from 8.2 million to 35.6 million tons. These increases are judged to be ambitious but achievable if good progress is made in increasing feed supplies, controlling animal disease, genetic improvement, institution strengthening, and establishing supportive economic policies. The most promising possibilities for sustainable increase in animal agriculture productivity include expansion and intensification of crop livestock systems in sub-humid and water portions of the semi-arid zone; increased productivity of mixed and specialized (eg. dairy) farming systems in the highland zone through technology transfer; and increased inputs and expansions of intensive commercial poultry and pig production.